The effects of age on DNA fragmentation, the condensation of chromatin and conventional semen parameters in healthy nonsmoking men exposed to traffic air pollution - Rubes, Jiri (Health Sci Rep, 2021)
BACKGROUND: Numerous studies have investigated age‐based declines in semen traits, but the impact of paternal age on semen parameter values remains inconclusive. OBJECTIVES: The aim of this study was to detect an impact of age on semen quality was studied in healthy nonsmoking men exposed to traffic air pollution. METHODS: Semen samples from 150 Prague City policemen aged 23 to 63 years were examined for standard semen parameters, sperm DNA fragmentation and high DNA stainability. RESULTS: A significant positive correlation was found between age and %DFI (r = .359, P < .001), and negative correlations were found between age and sperm vitality (r = −.247, P < .001), the % acrosome‐intact sperm (r = −.202, P = .013) and the % normal sperm heads (r = −.204, P = .012). A weak but significant negative correlation was found for high DNA stainability (% HDS) vs age (r = −.161, P = .050). No significant correlation was detected between male age and the other investigated semen quality parameters. At ages of 23 to 30, 31 to 40, 41 to 50, and 51 to 63 years, the mean %DFI values were 12.7 ± 7.18, 14.7 ± 7.42, 19.6 ± 11.25, and 34.2 ± 15.08, respectively. CONCLUSION: Our study shows a strong relationship (P < .001) between the age of men and sperm DNA fragmentation in an occupational cohort at risk of exposure to heavy traffic‐related air pollution in a large city center.